Effects of intravenous home dobutamine in palliative end‐stage heart failure on quality of life, heart failure hospitalization, and cost expenditure. (17th January 2018) - Martens, Pieter; Vercammen, Jan; Ceyssens, Wendy; Jacobs, Linda; Luwel, Evert; Van Aerde, Herwig; Potargent, Peter; Renaers, Monique; Dupont, Matthias; Mullens, Wilfried
Abstract: Aims: In patients with palliative end‐stage heart failure, interventions that could provide symptomatic relief and prevent hospital admissions are important. Ambulatory continuous intravenous inotropes have been advocated by guidelines for such a purpose. We sought to determine the effect of intravenous dobutamine on symptomatic status, hospital stay, mortality, and cost expenditure. Methods and results: All consecutive end‐stage heart failure patients not amenable for advanced therapies and discharged with continuous intravenous home dobutamine from a single tertiary centre between April 2011 and January 2017 were retrospectively analysed. Dobutamine (fixed dose) was infused through a single‐lumen central venous catheter with a small pump that was refilled by a nurse on a daily basis. Symptomatic status was longitudinally assessed as the change in New York Heart Association class and patient global assessment scale. Antecedent and incident heart failure hospitalizations were determined in a paired fashion, and cost impact was assessed. A total of 21 patients (age 77 ± 9 years) were followed up for 869 ± 647 days. At first follow‐up (6 ± 1 weeks) after the initiation of dobutamine, patients had a significant improvement in New York Heart Association class (−1.29 ± 0.64; P  < 0.001), global assessment scale (<0.001), and N‐terminal pro‐brain natriuretic peptide (6247 vs. 2543 pg/mL; P  = 0.033). Incident heart failure hospitalizations assessed at 3, 6, and 12 months were significantly reduced ( P  < 0.001 for all) in comparison with antecedent heart failure hospitalizations over the same time period. Cost expenditure was significantly lower at 3 ( P  < 0.001), 6 ( P  = 0.005), and 12 months ( P  = 0.001) after initiation of dobutamine. Mortality rate at 1 year was 48% with 9/12 (75%) patients dying at home, most often from progressive pump failure. Conclusions: Continuous intravenous home dobutamine in patients with palliative end‐stage heart failure is feasible and associated with improved symptomatic status, heart failure hospitalizations, and health‐care‐related costs. Nevertheless, results should be interpreted in the context of the small and retrospective design. Larger studies are necessary to evaluate the effect of dobutamine in palliative end‐stage heart failure.